Contribution to the tribe Apalochrini (Coleoptera, Melyridae, Malachiinae) of China, with notes on the genus Dicranolaius Champion and Intybia Pascoe - Jia-Xiao Sun; Zhenhua Liu; Bi Ding; Rongxiang Su; Guanmin Huang; Zhiyong Xue (Biodiversity Data Journal)
Apalochrini is a tribe of the family Melyridae characterised by the shortened pedicel, with 13 genera recorded in China at present. Dicranolaius Champion and Intybia Pascoe of Apalochrini are distributed in Asia and Southeast Asia, with the former genus extending to Australia, but not being found in China. In a recent expedition in the mangrove forests of Zhangzhou City (Fujian Province), eastern China, specimens of D. mangalicola Asano ＆ Kawashima, 2010 and I. swatowensis (Wittmer, 1956) were collected.Dicranolaius Champion is recorded from China for the first time and I. swatowensis is newly recorded for Fujian Province. Diagnostic characters of D. mangalicola is provided and I. swatowensis is re-described in details. An updated key to genera of the Chinese Apalochrini, based on male characters, is given.